"We'll starve to death": The consequences of COVID‐19 over the lives of poor people with disabilities in rural Nepal. Issue 2 (24th February 2022) - Sarker, Debashis; Shrestha, Sanjana; Tamang, Santosh Kumar Baidhya
Abstract: There is no doubt that the sudden outbreak of COVID‐19 negatively impacted billions of people worldwide, and among them, people with disabilities became most susceptible. However, little is known about the impact of COVID‐19 on the lives of people with disabilities in Nepal. Using empirical data from semi‐structured in‐depth interviews with people with disabilities, disability specialist, and community leaders, this study discusses the lived experiences of people with disabilities who have been affected by COVID‐19 in Nepal. This study revealed that the outbreak of COVID‐19 impacted people with disabilities by worsening their vulnerability. In particular, the majority of people with disabilities became further isolated, were disconnected from existing services such as access to information, education, and health care and many lost their income opportunities. Findings from this study further show that this pandemic affected the rights of people with disabilities guided by the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). Immediate financial and non‐financial support for people with disabilities from government and other stakeholders, such as non‐governmental organizations (NGOs), is needed, indicating the need for policymakers to reassess policies to ensure that they adequately protect the rights of people with disabilities.